Mountains as Earth’s Stakes in the Perspektive of the Qur’an: An Interdisciplinary Study of Qur’anic Exegesis and Geological Science - Mazaya Fuadaha; Faishal Abdullah (CV. Kalimasada Group, 2025)
This research examines the concept of mountains as Earth’s Stakes through an interdisciplinary lens, integrating Qur'anic perspectives with modern geological science. The study aims to bridge the gap between classical and modern exegesis (tafsir), specifically focusing on Tafsir Ibn Kathir and Quraish Shihab’s Tafsir Al-Misbah, and contemporary scientific understanding. The study employs an interdisciplinary approach, synthesizing qualitative textual analysis of religious scriptures with established scientific theories. It compares the linguistic and theological descriptions of mountains in the Qur'an (specifically Surah An-Naba: 6-7) with empirical geological data, including plate tectonics and the principle of isostasy. The results indicate that the Qur'anic term